2014
DOI: 10.1007/s11071-014-1814-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of nonlinear viscous damping on vibration isolator

Abstract: In this paper, vibration isolator of single degree of freedom systems having a nonlinear viscous damping is studied under force excitation. Stability of the steady state periodic response has been discussed. The influence of damping coefficients on the force transmissibility and displacement transmissibility is investigated. The relationship between amplitude and frequency is derived by using the averaging method. Results reveal that the performance of the nonlinear isolator has some beneficial effects compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…are the coefficients in the representation of (24). Moreover, the coefficients in (24) can be determined as…”
Section: Determination Of the Ofrfs Described By A More General mentioning
confidence: 99%
See 2 more Smart Citations
“…are the coefficients in the representation of (24). Moreover, the coefficients in (24) can be determined as…”
Section: Determination Of the Ofrfs Described By A More General mentioning
confidence: 99%
“…For example, Peng and Lang [21] have derived a recursive algorithm to determine the structure of the OFRF for the system described by a nonlinear differential equation model. More recently, the OFRF based approach has been applied in the analysis and design of nonlinear vibration isolators [22][23][24]. For example, by using the OFRF, Lang et al [22] and Peng et al [23] have rigorously proved significant beneficial effects of nonlinear damping on vibration isolation systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that applying nonlinear viscous damping can improve the isolation performance over a wide frequency range. Lv and Yao 20 further studied the effects of nonlinear viscous damping with displacement- n th power on the vibration isolator. Besides, Huang et al 21 investigated the effects of the velocity-displacement-dependent nonlinear damping on the isolation performance theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional passive isolators such as metal coil spring and rubber are generally soft for vibration isolation at relatively low frequencies, which is not expected in practice [14]. Nonlinear stiffness and nonlinear damping have been recently reported to be beneficial to vibration isolation for low and high frequencies [15][16][17]. For microvibration isolation, liquid damping is generally applied, in which no dead zone of friction exists, thereby benefiting small amplitude vibration isolation [18].…”
Section: Introductionmentioning
confidence: 99%